Contemporary animal advocacy in Italy. Issue 1 (25th July 2018) - Bertuzzi, Niccolò
Abstract : In spite of the great tradition in social movement studies, Italy completely lacks any contribution regarding animal advocacy from the point of view of political sociology. This is despite the fact that, as in the rest of Western societies, interest in the wellbeing, rights and status of non-human animals is growing. This can be seen both among the general population and in the very varied organised forms of welfare and activism. In this article, we will investigate this internal differentiation, starting from an initial stratification in welfare, protectionism and anti-speciesism, and focusing in particular on the following two aspects: ethical values; and political 'careers' and multi-membership affiliations. The investigation was accomplished by means of 20 semi-structured interviews and an online questionnaire answered by 704 volunteers and activists. The tripartition hypothesised was confirmed, although with a few exceptions: more progressive values emerged among anti-speciesists, and conservative positions among protectionists and welfarists, but the overall spectrum is characterised by utilitarian perspectives. Similarly, previous experience in the specific field of animal advocacy is typical of the protectionist area, while anti-speciesists also come from other opposition movements. Italian summary: Nonostante la notevole tradizione italiana di studi sui movimenti sociali, mancano contributi inerenti il cosiddetto movimento animalista dal punto di vista della sociologia politica. D'altra parte, come nel resto delle società occidentali, in Italia si registra un crescente interesse per il benessere, i diritti e lo status degli animali non umani. Questo fenomeno si può riscontrare sia tra la popolazione generale sia nelle svariate forme di attivismo emergenti. In questo articolo, studieremo questa differenziazione interna, partendo da una suddivisione iniziale in tre strati – cura, protezionismo e antispecismo – e concentrandoci in particolare su due aspetti: da una parte, valori etici; dall'altra, le 'carriere' politiche e le multi-appartenenze di attivisti e volontari. Per farlo utilizziamo 20 interviste semi-strutturate e un questionario online a cui hanno risposto 704 attivisti e volontari. La tripartizione ipotizzata è confermata, anche se con alcune eccezioni rispetto a specifiche dimensioni indagate: valori più progressisti sono emersi tra gli antispecisti e posizioni conservatrici tra protezionisti e membri dell'area della cura, mentre tutto lo spettro è caratterizzato da prospettive utilitaristiche. Allo stesso modo, le precedenti esperienze in campo animalista sono tipiche dell'area protezionista, mentre gli antispecisti provengono anche da altri movimenti antagonisti.